The Origins, Evolution, and Political Consequences of Britain's New Catholic Policy, From the Conquest of Quebec to the Eve of the American Revolution, 1759-1774 - Herdeck, Margaret Laniak (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2022)
Drawing on archival and printed primary collections from Canada, the United States, Ireland, France, Italy and the United Kingdom, and the work of historians throughout many of these communities, the thesis traces the origins, evolution and political consequences of Britain's historic recognition of Roman Catholicism in 1774, a decade following its victory over France in the Seven Years War. The thesis shows how the new policy arose directly out of Britain's conquest of French Catholic Canada in 1759/60 and the strategies adopted by Canadian church leaders during and after the conquest to protect the free exercise of their religion and their people's pre-conquest civil laws and customs. The Quebec Act enacted in June 1774 not only guaranteed the free exercise of the Roman Catholic religion in Canada, however, but the thesis argues that George III's government envisioned a broader application of its new Catholic policy beyond Canada, contrary to the views of some leading imperial historians that it was simply a `realistic and tolerant attempt to deal with an alien population' in a newly conquered territory. The best evidence, the thesis argues, that a broader application of its new statutorily-rooted tolerance of Roman Catholicism was intended is found in the history of the enactment of the Irish Oath Act given royal assents three weeks before the Quebec Act in June 1774. The Irish statute offered Ireland's Catholic millions an oath of allegiance that did not require them to deny the basic tenets of their faith as existing oaths did, opening the way ultimately to the full restoration of civil, political and religious rights to Ireland's Catholics. Lastly, the thesis presents a comprehensive analysis of the political impact of the new Catholic policy on the still virulently anti-Catholic Protestant American colonies, already in a rolling rebellion against the colonial policies of the imperial government. The fifty-six delegates sent to Philadelphia from twelve American colonies in September 1774 to develop a united plan of action against the recently enacted Coercive Acts also debated the political and military implications of the Quebec Act in particular on their future security in the British empire. In the end, the American leaders took a leaf out of their imperial government's playbook on the Canada question and invited their old French Catholic enemies to join in the evolving fight against Great Britain. The Canadians declined the offer, but also chose to withhold their support from both sides in the coming American Revolution, further evidence that notwithstanding their inferior status as a conquered people in an alien culture different in language, customs and religion from their own, they continued to insist successfully on shaping their own destiny.
APPROVED
Keywords: Quebec Act of 1774; Irish Oath Act of 1774; French Canada 1759 to 1774; Catholic policy and the American Revolution; British Catholic Policy in 1774